2021
DOI: 10.1016/j.jbc.2021.101385
|View full text |Cite
|
Sign up to set email alerts
|

The minimal structure for iodotyrosine deiodinase function is defined by an outlier protein from the thermophilic bacterium Thermotoga neapolitana

Abstract: The nitroreductase superfamily of enzymes encompasses many flavin mononucleotide (FMN)-dependent catalysts promoting a wide range of reactions. All share a common core consisting of an FMN-binding domain, and individual subgroups additionally contain one to three sequence extensions radiating from defined positions within this core to support their unique catalytic properties. To identify the minimum structure required for activity in the iodotyrosine deiodinase subgroup of this superfamily, attention was dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Protonation of the aromatic ring of I-Tyr is an obvious process that can limit turnover since the loss of aromaticity is highly endergonic even for the electron-rich systems such as a phenol. Since no proton donor has yet been identified in the active sites of various IYDs, ,,, site-directed mutagenesis is ineffective for examining such protonation. However, the contribution of proton transfer to the overall rate of turnover can be measured by solvent kinetic isotope effects irrespective of the specific donor.…”
Section: Resultsmentioning
confidence: 99%
“…Protonation of the aromatic ring of I-Tyr is an obvious process that can limit turnover since the loss of aromaticity is highly endergonic even for the electron-rich systems such as a phenol. Since no proton donor has yet been identified in the active sites of various IYDs, ,,, site-directed mutagenesis is ineffective for examining such protonation. However, the contribution of proton transfer to the overall rate of turnover can be measured by solvent kinetic isotope effects irrespective of the specific donor.…”
Section: Resultsmentioning
confidence: 99%
“…However, this leads to a broader question about the extent to which the functional importance of residues may correlate to their conservation in certain subfamilies or throughout an entire superfamily of proteins. Already, our laboratory has demonstrated that an active site loop in IYD was not necessary for dehalogenation despite its predominance in the IYD subfamily . We have now generalized this analysis in the current report to evaluate if the dominance of a particular residue common to most of the NTR superfamily is necessarily linked to a functional imperative.…”
Section: Introductionmentioning
confidence: 74%
“…Bulk solvent could suppress such an effect in many enzymes but is excluded in IYD when the substrate is bound and the active site lid is closed. 11,19,27…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations